2015
DOI: 10.1094/pdis-02-15-0218-re
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting Fungicide-Based Management Guidelines for Leaf Blotch Diseases in Soft Red Winter Wheat

Abstract: Standard foliar fungicide applications in wheat are usually made between flag leaf emergence (Feekes [FK] 8) and heading (FK10.5) to minimize damage to the flag leaf. However, over the last few years, new fungicide programs such as applications prior to FK8 and split half-rate applications have been implemented, although there are few data pertaining to the efficacy of these programs. Eight experiments were conducted in Illinois, Indiana, Ohio, and Wisconsin from 2010 to 2012 to compare new programs to standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 34 publications
0
5
0
2
Order By: Relevance
“…Previous research in Michigan, Kansas, and Wisconsin has shown that the inclusion of foliar fungicide can protect wheat from disease and lead to higher yields, but the resulting economic returns were variable (Jaenisch et al, 2019;Quinn & Steinke, 2019;Roth et al, 2020). Willyerd et al (2015) reported that in Ohio and states in the Midwest, the efficacy and profitability of applying a foliar fungicide to wheat varied with the application rate and timing. Susceptible wheat cultivars also benefit more from a foliar fungicide application compared with resistant cultivars (Cruppe et al, 2021).…”
Section: Core Ideasmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research in Michigan, Kansas, and Wisconsin has shown that the inclusion of foliar fungicide can protect wheat from disease and lead to higher yields, but the resulting economic returns were variable (Jaenisch et al, 2019;Quinn & Steinke, 2019;Roth et al, 2020). Willyerd et al (2015) reported that in Ohio and states in the Midwest, the efficacy and profitability of applying a foliar fungicide to wheat varied with the application rate and timing. Susceptible wheat cultivars also benefit more from a foliar fungicide application compared with resistant cultivars (Cruppe et al, 2021).…”
Section: Core Ideasmentioning
confidence: 99%
“…Many farmers in Ohio use foliar fungicide to control diseases throughout the growing season. Farmers commonly apply foliar fungicide at the Feekes 9 growth stage to protect the flag leaf from Septoria leaf blotch, Stagonospora leaf blotch, tan spot, leaf rust, and powdery mildew, or at Feekes 10.5.1 to protect against Fusarium head blight (FHB) and Stagonospora glume blotch (Bhathal et al., 2003; Cook et al., 1999; Jaenisch et al., 2019; Lackermann et al., 2011; Paul et al., 2018; Willyerd et al., 2015). Previous research in Michigan, Kansas, and Wisconsin has shown that the inclusion of foliar fungicide can protect wheat from disease and lead to higher yields, but the resulting economic returns were variable (Jaenisch et al., 2019; Quinn & Steinke, 2019; Roth et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Statistical analysis was used to explain relationships between plant disease management and associated yield or yield quality [25][26][27][28], as done previously in wheat and barley [8,[29][30][31][32]. A mixed effects model was made for the relationship between DON production and FHB presence [33,34].…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Šķirnes ieņēmībai pret lapu plankumainībām ir būtiska nozīme, taču slimības attīstība šķirnēm dažādos vides apstākļos var atšķirties (Willyeard et al, 2015). Slimības attīstība ir atkarīga no vides apstākļiem konkrētā laukā.…”
Section: Agrotehnisko Pasākumu Ietekme Uz Lapu Slimību Attīstībuunclassified